Wymiar sprawiedliwości przyjazny dziecku — perspektywa prawno-psychologiczna - Skubisz-Ślusarczyk, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
From a psychological perspective, a child hearing is a special form of interaction betweenan adult person and a child. The article is presenting the proposition of a child hearing method, which allows the judge to acquire important information for the proceedings outcome, on the minor and its needs, as well as not to involve the minor in its parent’s conflict, and does not burden him with the responsibility for the judge’s decisions. The elaborations were supplemented with a presentation empirical finding concerning the said legal institution.
Keywords: psychologia; prawa dziecka; przesłuchanie dziecka; ochrona dziecka w postępowaniu cywilnym; ochrona dziecka w postępowaniu karnym